Kebijakan Penguatan Kewajiban Alih Pengetahuan Tenaga Kerja Asing - Solechan Solechan (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2018)
This study aims to find out the policy of transfer of knowledge of foreign workers in Indonesia. In addition, to know the policy of transfer of knowledge on the labor legislation law has guaranteed the implementation of knowledge transfer in the framework of the protection of Indonesian labor force. Research method in this research is legal research (legal research), that is by using library research data (library research), using statutory approach approach (statutory approach). The results showed that the transfer of knowledge has been regulated in the legislation in Indonesia. But the arrangement is still very general and sectoral. Keywords: Transfer of Knowledge, Manpower, Policy